Primary extranodal NK/T cell lymphoma: A rare cutaneous malignancy - Shirazi, Nadia; Jindal, Rashmi; Ahmad, Sohaib; Chauhan, Neena (Asian Journal of Medical Sciences, 2017)
Extranodal Natural Killer cell/T cell lymphomas are subcategorized into ENK/T-nasal and ENK/T-nasal type. These lymphomas presenting as initial involvement of skin are unusual and are known as Primary cutaneous NK/T – nasal type lymphomas. We present a rare case of a middle aged female presenting with rapidly developing skin nodules and ulcers. This case highlights the fact that adequate work up should be done in all such cases to avoid erroneous diagnosis and subsequent inadequate treatment of primary cutaneous lymphoma patients. Asian Journal of Medical Sciences Vol.8(1) 2017 91-93